Pengembangan Media Pembelajaran Pendidikan Agama Islam dan Budi Pekerti Berbasis Web Kelas XIPA di SMAN 1 Enrekang - Firqa Najiah, Nur; Fakhrunnisaa, Nur; Assafari, Amir Faqihuddin (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
This research discusses the development of web learning of Islamic Religious Education and ethics subjects based on web class X IPA at SMAN 1 Enrekang to determine the level of validity of this product. This type of research is R&D (Research and Development) research using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Students of X MIPA VI class of SMAN 1 Enrekang will be the subject of the research. Data collection techniques were obtained through documentation, interviews, and questionnaires. The data were analyzed using a process called quantitative descriptive analysis. The research results of web learning developed by researchers obtained validation results from media experts as much as 94%, with a classification of